Abiotic and Biotic Soil Legacy Effects of Plant Diversity on Plant Performance - Kostenko, Olga; Bezemer, T. Martijn (Frontiers in Ecology and Evolution, 2020)
Soil legacies are typically examined for individual plant species, and we poorly understand how soil legacy effects created by entire plant communities influence plant growth. We used soils collected from a biodiversity field experiment to examine how the soil legacy effects of plant diversity influence the growth of a focal plant species. In the field, we experimentally assembled and maintained grassland communities (0, 1, 2, 4 or 9 species) for two years. We collected soil from all plots and examined the growth of Jacobaea vulgaris in these soils under controlled conditions, and compared this to the performance of individuals that were planted directly in the plots. J. vulgaris was not part of the species pool used in the biodiversity experiment, but commonly occurs in the area. To disentangle different components of the legacy effects (soil nutrients vs soil biota), in the pot experiment we tested the effects of plant growth in pure field soil and in sterilized background soil inoculated with live or with sterilized field soil. We found a weak positive legacy effect of plant diversity on J. vulgaris root biomass, but only in pure field soil and not in the inoculated treatments. Interestingly, for individuals planted in the field plots, plant biomass was negatively related to the diversity of the surrounding plant community but this was mainly due to high biomass in bare plots. In the pot experiment, plant biomass also varied among soils collected from different monocultures. Soil fungal community composition was not affected by the diversity of the plant community, but the biomass of the plants grown in pots with pure field soil correlated with fungal composition. The biomass of plants grown in pure field soil was also positively correlated with nitrogen availability in the soil, and negatively with the cover of three plants species in the communities. In conclusion, our study does not provide strong evidence for an important role of plant diversity on soil legacy effects on J. vulgaris, and shows that for this plant species, performance is related to both the biotic and abiotic characteristics of the soil in which it grows.